Beyond the Marriage Metaphor: Nation, Violence, and the Fallen Woman in The Canadian Brothers - Rothenburger, Sunnie (Studies in Canadian Literature, 2008)
In John Richardson’s historical novel The Canadian Brothers (1840), Matilda Montgomery is constructed as sexually and morally fallen, and commentators have seen her merely as a demonic representation of the sinful United States. However, unlike most fictional fallen women, as characterized by scholars such as Amanda Anderson and Nina Auerbach, Matilda finds power in her condition; her representation challenges dualistic nineteenth-century stereotypes about women, as well as suppositions about nationalism. In large part, this interrogation is accomplished by the novel’s challenging of the conventions of national allegory, especially what Carl Murphy calls the "marriage metaphor," in which a man and woman of different nationalities join in a romantic union, suggesting a similar international harmony. Matilda shows both gendered and national identities to be performative, in Judith Butler’s sense, and demonstrates how the fallen woman has the potential to subvert sexist and nationalist claims.